2013
DOI: 10.5194/acp-13-1569-2013
|View full text |Cite
|
Sign up to set email alerts
|

Sources of anions in aerosols in northeast Greenland during late winter

Abstract: The knowledge of climate effects of atmospheric aerosols is associated with large uncertainty, and a better understanding of their physical and chemical properties is needed, especially in the Arctic environment. The objective of the present study is to improve our understanding of the processes affecting the composition of aerosols in the high Arctic. Therefore size-segregated aerosols were sampled at a high Arctic site, Station Nord (Northeast Greenland), in March 2009 using a Micro Orifice Uniform Deposit I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 41 publications
5
15
2
Order By: Relevance
“…During the entire campaign, SO4 2is the dominant species that on average makes up almost 70% of the 295 PM1 mass concentration measured by the SP-AMS (average 1.5 µg m -3 , Figure 1.b-c). This is in accordance with previous findings for SO4 2at VRS based on measurements with lower time-resolution (Nguyen et al, 2013;Fenger et al, 2013;Heidam et al, 2004). Atmospheric SO4 2is mainly formed as secondary inorganic aerosols and only a minor fraction is from primary emissions (Massling et al, 2015).…”
Section: Time Series 280supporting
confidence: 94%
See 1 more Smart Citation
“…During the entire campaign, SO4 2is the dominant species that on average makes up almost 70% of the 295 PM1 mass concentration measured by the SP-AMS (average 1.5 µg m -3 , Figure 1.b-c). This is in accordance with previous findings for SO4 2at VRS based on measurements with lower time-resolution (Nguyen et al, 2013;Fenger et al, 2013;Heidam et al, 2004). Atmospheric SO4 2is mainly formed as secondary inorganic aerosols and only a minor fraction is from primary emissions (Massling et al, 2015).…”
Section: Time Series 280supporting
confidence: 94%
“…A major part of the aerosol mass is long-range transport from source regions outside the Arctic where the primary source region has been identified as the northern part of Eurasia (Nguyen et al, 2013;Quinn et al, 2008;Heidam et al, 2004;Stohl et al, 2007;Christensen, 1997). Studies have shown that main constituents of Arctic aerosols are sulfate (SO4 2-) and organics mixed with a minor fraction of nitrate 70 (NO3 -), ammonium (NH4 + ), black carbon (BC) and heavy metals (Quinn et al, 2007;Fenger et al, 2013;Nguyen et al, 2013;Frossard et al, 2011;Barrie et al, 1981). This is also the case at the high Arctic station, Villum Research Station (VRS) at Station Nord in North Greenland, where this study was conducted.…”
Section: Introductionmentioning
confidence: 99%
“…These fragments are often taken as being indicative of anhydrous sugar such as levoglucosan and thereby suggest that biomass burning makes some contribution to Arctic OA. However, SOA also contributed to the abundance of C 2 H 4 O + 2 (Aiken et al, 2008Cubison et al, 2011;Lee et al, 2010;Saarnio et al, 2013). Quantitatively, the expected abundance of C 2 H 4 O + 2 from SOA did not exceed the measured concentration in this study.…”
Section: Source Apportionmentcontrasting
confidence: 41%
“…While Roscoe et al . [] found that frost flowers were very stable at high wind speeds up to 12 m s −1 , this might have been because the laboratory conditions were not representative of the Arctic [ Fenger et al ., ]. Yang et al .…”
Section: Introductionmentioning
confidence: 99%
“…An alternative is that frost flowers may contribute to the high salt loading during winter and early spring in polar regions when young sea ice (e.g., nilas, leads) replaces open water near coastal sampling sites [Rankin et al, 2000[Rankin et al, , 2002Rankin and Wolff, 2003]. While Roscoe et al [2011] found that frost flowers were very stable at high wind speeds up to 12 m s À1 , this might have been because the laboratory conditions were not representative of the Arctic [Fenger et al, 2013]. Yang et al [2008] suggested blowing snow as a potential aerosol source, while Nghiem et al [2012] challenged this view for the Arctic.…”
Section: Introductionmentioning
confidence: 99%